2020
DOI: 10.3389/fpls.2020.00825
|View full text |Cite
|
Sign up to set email alerts
|

Raising the pH of the Pulsing Solution Improved the Acropetal Transport of NAA and 2,4-D and Their Efficacy in Reducing Floret Bud Abscission of Red Cestrum Cut Flowers

Abstract: The use of auxins to improve the vase life of cut flowers is very limited. Previous studies demonstrated that a pulse treatment of Red Cestrum (Cestrum elegans Schlecht.) cut flowers with 2,4-dichlorophenoxyacetic acid (2,4-D) significantly reduced floret bud abscission, whereas 1-naphthaleneacetic acid (NAA) was ineffective. This difference resulted, at least in part, from the higher acropetal transport capability of 2,4-D compared to that of NAA. The present research focused on examining the factors affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In contrast, in Expt. 2, the stems were tapped three times to remove abscised petals before recording flower longevity each day (Abebie et al, 2008(Abebie et al, , 2020Setyadjit et al, 2004). Flower diameter was recorded for any open flower in Expt.…”
Section: Assessments (Expts 1 and 2)mentioning
confidence: 99%
“…In contrast, in Expt. 2, the stems were tapped three times to remove abscised petals before recording flower longevity each day (Abebie et al, 2008(Abebie et al, , 2020Setyadjit et al, 2004). Flower diameter was recorded for any open flower in Expt.…”
Section: Assessments (Expts 1 and 2)mentioning
confidence: 99%
“…It has also been reported that a pulse treatment of red cestrum (Cestrum elegans Schltdl.) cut flowers with 2,4-dichlorophenoxyacetic acid (2,4-D) significantly reduced floret bud abscission, whereas NAA was ineffective (Abebie et al, 2020). In another study, Khandaker et al (2017) showed that spraying the plant with 25 mg/L NAA enhanced the growth and development of the Mokara Chark Kuan orchid cut flower.…”
Section: Introductionmentioning
confidence: 99%